PEMBERDAYAAN UMKM JASA AKOMODASI WISATA DI UBUD SEBAGAI DAERAH WISATA DENGAN PENERAPAN E-COMMERCE MELALUI SITUS PORTAL PARIWISATA - Kadyanan, I.G.A.G.A.; Muliantara, A.; Widiartha, I.M.; Mahendra, I.B.M. (Buletin Udayana Mengabdi; Vol 16 No 2 (2017), 2017)
Ubud is an area with tremendous tourist charm. Many sights and attractions of the entertainment provided. Along with the development of the tourism industry, many related businesses such as tourism accommodation provided homestay and bungalows. This raises the tight competition among the actors of tourism in Ubud as the innkeeper (homestay, bungalows, villas). Partners in this activity were Mr. I Ketut Sudarsana, as the owner of Pondok Bambu Homestay and Mr I Wayan Pering Sanjaya as owner Pering Bungalow. Based on interviews with both partners, the income of both partners is uncertain, as it depends on the level of occupancy. Besides revenue fluctuations are also influenced by marketing is still not optimal. Often, the benefits will not be able to cover the operating costs of lodging (during Low Season). The lack of supporting facilities such as transportation, access to wi-fi, travelers also causes less keen to stay. In this activity will be pursued several things including identifying needs, the design of which the mechanism of online marketing (utilizing a number of tourism portal online), designing a marketing strategy by teaming up online with several tourism agencies. With the hope of profit achieved by the two partners can be increased and more stable. This program was conducted for eight months by the amount of activity budget Rp. 9.000.000.00.